Application software information risk management - Корнієнко, Богдан Ярославович; Максімов, Юрій Олександрович; Марутовська, Наталія Миколаївна (Ukrainian Information Security Research Journal, 2012)
The article describes the software analysis and management of information risks. Get a clear structure of the functioning of the program: solved algorithmic design principles, formats, templates, graphics, interfaces, management practices and determine the threat level of risk. Analyzed software information risk management for compliance with basic international standards of information security.